Religious Coping and Challenges Among Displaced Muslim Female Refugees. Issue 4 (November 2019) - Shaw, Stacey A.; Peacock, Laurel; Ali, Latifa Mahram; Pillai, Veena; Husain, Altaf
With millions of women experiencing forced displacement, attention is needed toward migrant women's lived experiences. Religion is an understudied but central component of coping for many migrant women. Through the use of qualitative and quantitative methods, an exploratory study was conducted with 36 forced migrant Shia Muslim women residing in a predominantly Sunni Muslim country of first asylum. Using the brief Multidimensional Measure of Religiousness/Spirituality and drawing from feminist theory, intersectionality, and the ecological framework, we describe women's experience with religion and spirituality across a variety of domains. Open-ended semistructured interviews were analyzed using a thematic analysis approach. Participants were highly religious across all domains measured. Key themes emerged related to how religion helps women manage stress, including: (1) trusting God to solve problems and (2) relying on prayer and other religious practices to cope. Despite these strengths, women also described major challenges to religious practice, where the third identified theme emphasized that fear and persecution limit religious practice. This article builds understanding of forced migrant women's experiences, with implications for social work practice and immigration policy. Service organizations can recognize and support religious coping, particularly among religious minority refugee women. Additionally, practitioners and policy makers can promote religious tolerance and understanding within diverse host communities.